Tai Chi enhances cognitive training effects on delaying cognitive decline in mild cognitive impairment. Issue 1 (15th March 2022) - Li, Binyin; Tang, Huidong; He, Guiying; Jin, Zhijia; He, Yixi; Huang, Pei; He, Naying; Chen, Shengdi
Abstract: Introduction: Cognitive training and physical exercise have shown positive effects on delaying progression of mild cognitive impairment (MCI) to dementia. Methods: We explored the enhancing effect from Tai Chi when it was provided with cognitive training for MCI. In the first 12 months, the cognitive training group (CT) had cognitive training, and the mixed group (MixT) had additional Tai Chi training. In the second 12 months, training was only provided for a subgroup of MixT. Results: In the first 12 months, MixT and CT groups were benefited from training. Compared to the CT group, MixT had additional positive effects with reference to baseline. In addition, Compared to short‐time training, prolonged mixed training further delayed decline in global cognition and memory. Functional magnetic resonance imaging showed more increased regional activity in both CT and MixT. Discussion: Tai Chi enhanced cognitive training effects in MCI. Moreover, Tai Chi and cognitive mixed training showed effects on delaying cognitive decline.